Field Trip as a Challenging Method in Developing Students’ Mastery of Descriptive Texts - Indrawati Indrawati (Edukasi, 2020)
Field trip method is believed to have power in increasing students’ drive in writing, especially when they are asked to describe things or people. The purpose of this quasi-experimental research was to gain as much as information about the use of Field Trip Method in developing learners’ ability in writing descriptive texts for tenth graders of SMA Negeri I Mendo Barat, Bangka. A writing test was conducted to collect the data. Based on the findings, the mean score of post-test in the class which was given treatment was higher (70.27) compared to the mean score in the class with no treatment (60.22). In addition, comparing the post-test between the two groups using Independent Sample T-test, it was found that T-table was lower than T-obtained, and the Paired Sample T-test also revealed a significant difference between the pre-test and the post-test in the experimental group. It is obviously seen that there was an absolute distinction between those two classes, and it can be concluded that Field Trip Method can improve the students’ skill in producing descriptive text at SMA Negeri 1 Mendo Barat.